(3bUGFOs - (3LQhd Hf ChS Hf eGdc GdYHSj (B((3GdoMWjFI(B)s
(3ChdgG (B:s
(3bGd WQaI Hf GdYHO dNhdg CWdGd HHQbg KgeO hbaJ HgG CHcj hCHcj Edi GdZO hbhakG HgG UMHi Ydi eWjge jbhdhf dG Jgdc CSi hJLdO s
(3BNQgG (B:s
(3hjYRdfj CHfGA SYO Ydjge heG bdJ EdG HGdPj YdeJ SYO s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdQGHYs
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3hYdjgG HYV GdTQhMs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs